Mosque economic empowerment through sharia microfinance institutions - Afdhal Yaman (Balai Diklat Keagamaan Ambon, 2024)
Mosques are not only places of worship but also places of economic activity. The potential for economic empowerment in mosques has not been realized optimally. As part of strengthening the community's economy, the role of mosques in society needs to be expanded. This research is qualitative research with the type of research, namely literature study, which uses data sources in the form of reference books and scientific journal articles. The results of this research indicate that mosque-based community economic empowerment is very necessary as a driving force for poverty alleviation efforts to improve the quality of life of the community. By making maximum use of the function and potential of mosques, the Mosque's economy can be strengthened and used as a strategic location for the economic development of the local community.